ANALISIS DAMPAK NEGATIF FACEBOOK PADA REMAJA KELAS X IPS SMA KEMALA BHAYANGKARI KUBU RAYA - Malindo, Hari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The negative impact of the use of facebook is a result caused the use of facebook excessively that can give rise to abuse and diversion to brpengaruh directly to the consumer, and often waste time just to tamper with his facebook account, if not used wisely facebook will have a negative impact to pengggunanya it sendiri..Oleh because the researchers wanted to know more profound analysis of the negative impact on teenagers facebook IPS class X SMA Kemala Bhayangkari Kubu Raya.A common problem in this research is